The grieving process - Kay, Libby; HSTN (Carrollton, TX : PRIMEDIA Workplace Learning, 2002)
The grieving process is natural and can be experienced as result of numerous circumstances including death of a loved one, loss of a limb or significant changes in a living situation. This program describes the stages of the grieving process- denial, anger, bargaining, depression and acceptance. Each stage is normal and must be experienced prior to moving on to the next step and to completion. Common behaviors observed during each stage are presented along with strategies for the healthcare professional to incorporate in his or her care of the grieving person
'Month of June 2002, tape 13' --Label
Approved for CE credit
Libby Kay
VHS
Keywords: Grief